The effect of giving red ginger drinks (zingiber officinale var. Rubrum) on dysmenorrhea complaints in female students class of 2020 FK UMI - Ida Royani; Vira Rosa Riani; Zulfitriani Murfat; Fadli Ananda; Irmayanti Haidir Bima (Sean Institute, 2024)
Dysmenorrhea is one of the diseases most commonly suffered by adolescent girls and is still a problem throughout the world. There are several methods that can be used to treat dysmenorrhea complaints, including administering drugs both pharmacological and non-pharmacological (herbs). Non-pharmacological treatments that are considered to help reduce dysmenorrhea complaints include the red ginger plant. This ginger drink has body warming, anti-rheumatic, anti-inflammatory and analgesic properties. Shogaol and gingerol compounds have the effect of reducing pain or soreness. To find out the effect of giving red ginger drink on complaints of dysmenorrhea in students of the 2020 class of FK UMI.Experimental research with a Quasi Experimental research design with a pre-post test only control group design. There was a change in menstrual abdominal pain (dysmenorrhea) in the Class of 2020 FK UMI students after giving red ginger drink, namely 12 respondents who experienced pain disappeared (40.0%), 11 respondents who experienced mild pain (36.7%) There were 4 respondents who experienced moderate pain (13.3%) and 3 respondents who experienced no change (10.0%). Red ginger drink (Zingiber officinale var. Rubrum) can relieve menstrual stomach pain (dysmenorrhea) for students of the Class of 2020 FK UMI.